Experimental Study and Theoretical Verification of Explosion-Proof Performance of Insulated Glass. (18th May 2020) - Zhang, Jinju; Wang, Xinjian; Wang, Liqiong; Su, Pengchong
Abstract : Building glass fragment in a blast-related environment is the main cause of casualties. In order to analyze the explosion-proof performance of insulated glass quantitatively in conventional buildings, the explosion experiment under different shock wave loads was carried out on the insulated glass, the pressure sensor was used to collect the overpressure value of the explosion shock wave, and the high-speed camera was used to record the breaking process of glass. The broken state of the insulated glass and the critical overpressure value of the broken state under different working conditions were obtained. And the theoretical calculation method based on the equivalent static load was used to verify the critical overpressure value of the insulated glass. The research showed that the fragments scattered toward the center of the explosion source when the layer of the insulated glass face to the explosion wave front was broken, and the fragments mainly scattered in the direction of the shock wave propagation when it was completely broken. The theoretical calculation method based on the equivalent static load could be used to evaluate the explosion-proof performance of the insulated glass.